A STUDY ON HEALTH ISSUES FACED BY EMPLOYEES OF FIREWORK INDUSTRIES IN VIRUDHUNAGAR DISTRICT - Arul, S. Muthu; K. Rajamannar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Health related problems has become a common phenomenon in the firework industries. Whatever, preventive measures the employees took, it did not help them much in protection. In these fireworks industries, employee’s health is rehabilitated into wealth to protect their family. Fireworks employees face many health issues like Respiratory problems, Skin Problems, Muscle strain problems, Heart problems and Ortho problems. The main aim of this paper is to analyse the health issues faced by the fireworks employees in Virudhunagar District. This paper consist of both primary and secondary data. Primary data is collected from 200 employees from Sivakasi and Sattur working in fireworks industries by using convenient sampling methods. Statistical tools like, percentage analysis, weighted average method and kruskal wallis test are used to analyse the collected data. The study found that there is a significant relationship between the socioeconomic profile (age and gender) and the health issues of employees in fireworks industries, and most importantly there is a significant relationship between the year of experience and health issues of employees in fireworks industries.